The Evidence Room - Bordeleau, Anne 1972- (University of Toronto Press, 2016)
Internationally renowned and award-winning historian Dr. Robert Jan van Pelt's The Evidence Room is a chilling exploration of the role architecture played in constructing Auschwitz - arguably the Nazis' most horrifying facility